2016
DOI: 10.1002/ppsc.201600255
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Tunable Synthesis of Hollow Gold Nanospheres through Control of Reaction Temperature

Abstract: Here, it is demonstrated that the size tunable hollow gold nanospheres (HGNs) of ≈24–122 nm in diameter can be facilely achieved by controlling a signal parameter, reaction temperature, in the synthesis. The varied particle sizes of HGNs result in highly tunable surface plasmon resonance (SPR) absorption in the entire visible to near infrared region of the spectrum, with maximum peak position from 565 to 850 nm when the reaction temperature is varied from 80 to 10 °C. The particle size and structural propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Silver (Prevo et al, 2008; Schwartzberg, Olson, et al, 2006; Z.‐S. Zhang et al, 2010) and cobalt‐based (Adams et al, 2014; Glavee et al, 1993; Lindley et al, 2018; Masa et al, 2016; Pu et al, 2017; Schwartzberg, Olson, et al, 2006) nanoparticles are often used as templates for making HGNs because they have appropriate reduction potentials (0.7996 and −0.28 V, respectively) as compared to that of gold (1.498 V). While using silver as a template can yield NIR light absorbing particles, there has been less work done to optimize and fine tune their synthesis, and the particles tend to be more polydispersed (Prevo et al, 2008; Schwartzberg, Olson, et al, 2006; Z.‐S.…”
Section: Structural Control In Hgn Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Silver (Prevo et al, 2008; Schwartzberg, Olson, et al, 2006; Z.‐S. Zhang et al, 2010) and cobalt‐based (Adams et al, 2014; Glavee et al, 1993; Lindley et al, 2018; Masa et al, 2016; Pu et al, 2017; Schwartzberg, Olson, et al, 2006) nanoparticles are often used as templates for making HGNs because they have appropriate reduction potentials (0.7996 and −0.28 V, respectively) as compared to that of gold (1.498 V). While using silver as a template can yield NIR light absorbing particles, there has been less work done to optimize and fine tune their synthesis, and the particles tend to be more polydispersed (Prevo et al, 2008; Schwartzberg, Olson, et al, 2006; Z.‐S.…”
Section: Structural Control In Hgn Synthesismentioning
confidence: 99%
“…HGNs are solvent‐filled, hollow shells of gold with tunable SPR from 540 to 1000 nm (Lindley et al, 2018; Pu et al, 2017; Xie et al, 2013). Their tunability arises from changing the size and aspect ratio of the structure and allows them to be used in a large number of applications (Adams et al, 2014; Lindley et al, 2018; Schwartzberg, Olson, et al, 2006; Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One such factor is environmental oxygen. GE in HGN synthesis has traditionally been performed under aerobic conditions [31][32][33][34][35][36][37][39][40][41][42]45 with cobalt as a starting template because of its favorable reduction potential and ease of oxidation in air. 46−49 This ease of oxidation allows facile removal of residual core material after shell formation without relying on postprocessing techniques like wet-chemical etching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…44 Recently, Pu et al showed that reaction temperature may be used to slow nucleation and promote growth from 24 to 122 nm in diameter but some resultant particles were polydisperse and exact sizes were difficult to achieve reproducibly. 45 Although progress has been made, size control methods for cobalt-based NP systems remain limited and fine adjustments over a large size range have not been realized experimentally.For a given scaffold diameter, the SPR frequency and full width at half-maximum of the resultant HGNs are determined by their shell thickness and uniformity, structural parameters that are governed by the GE process. Previously, Schwartzberg et al showed that shell thickness could be increased simply by providing more gold during GE 31 but other factors affecting shell structure and uniformity have not been explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation